Antropologiczny wymiar wiary. Spojrzenie Jana Pawła II - Gryz, Krzysztof (Analecta Cracoviensia, 2012)
The article analyzes, on the basis if the private letters of John Paul II, the anthropological dimension of faith which is, for the Pope, the essential good of faith because it reveals the goodness of human nature as rational and free being, able to recognize the trans-phenomenological truth and able to choose in free act the recognized truth.In the act of faith, this human ability is actualized in the most basic and deepest way, because it concerns the absolute reality, that is, the Absolute God.This thesis finds its confirmation in the personal journey of faith enacted by John Paul II. This journey can be summarized in the following points: upbringing in a Christian family, intellectual selfformation and personal search for the truth about the sense of life, reading of the Bible, experience of conformity between faith and personal structure of man, and consciousness of passing away and the hope for everlasting life in unity with God.